Comparative study of the dust color temperature and dust mass within the isolated dust in W51 giant molecular cloud in IRIS and AKARI data - Paudel, M.S.; Kushuwala, H.K.; Bhattarai, S. (BIBECHANA, 2024)
This work presents the comparative study of the properties of dust within the W51 Giant Molecular Cloud (GMC) located at (RA, DEC) (J2000): 290.91°, +14.51°. In the infrared data of Improved Reprocessing of the IRAS (IRIS) the dust structure seems single and isolated having size 0.45°×0.45° but in AKARI infrared survey it breaks into two isolated regions having size 0.15°×0.15° and 0.10°×0.10°, represented by AKARI-I and AKARI-II respectively. In IRIS map, 60 and 100 mm and in AKARI map, 90 and 140 mm image are used for extraction of the infrared flux. The dust color temperature (Td) and dust mass (Md) are calculated from the infrared flux and found to 30.34 K in IRIS and 27.40 K and 23.55 K in AKARI-I and AKARI-II. A linear relationship between the infrared flux at two wavelength is found except AKADI-I. The dust mass per pixels in the isolated (core) region is found to be increase compare to total study region. To quantify the relation between flux, dust color temperature and dust mass the regression analysis is used and observed spectrum of relation. A huge SIMBAD background objected is found embedded in the dust cloud which might have been shaping the spatial variation of temperature and mass within dust cloud.